2019
DOI: 10.18632/oncotarget.26993
|View full text |Cite
|
Sign up to set email alerts
|

GPCR-mediated PI3K pathway mutations in pediatric and adult thyroid cancer

Abstract: Whole exome sequencing (WES) recently identified frequent mutations in the genes of GPCR-mediated PI3K pathway ( LPAR4 , PIK3CA , and PTEN ) in a Chinese population with papillary thyroid cancers (PTCs). The study found LPAR4 mutations as novel gene mutations in adult population with differentiated thyroid cancer (DTC). Here, we determine the prevalence of somatic mutations in this pathway ( LPAR4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Moreover, the mutational incidence of DTC-specific genes including BRAF, TERT, RAS and PIK3CA, in the Saudi Arabian cohort was comparable to that of the incidence of the Western cases (10,11,35). The limitation of this study is a failure to analyze the ALK gene fusion which is considerably detected in thyroid cancers (9,27).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, the mutational incidence of DTC-specific genes including BRAF, TERT, RAS and PIK3CA, in the Saudi Arabian cohort was comparable to that of the incidence of the Western cases (10,11,35). The limitation of this study is a failure to analyze the ALK gene fusion which is considerably detected in thyroid cancers (9,27).…”
Section: Discussionmentioning
confidence: 80%
“…Two other more aggressive subtypes of thyroid cancer include the poorly differentiated (PDTC) and anaplastic thyroid cancer (ATC) (4). Genetic alterations in DTC involve many genes and include RET/PTC, BRAF, RAS, PAX8/PPAR-γ, EGFR, EIF1AX, PPM1D, CHEK2, with a low prevalence of PIK3CA and PTEN genes (5)(6)(7)(8)(9)(10)(11). TERT promoter mutations have been demonstrated to be a major determinant of poor outcomes in DTCs (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their broad physiological and pathological functions, as well as acting as favorable sites for drug development, the roles of GPCRs have been underappreciated for a long time in tumor biology ( 83 ). With the discovery of more GPCRs associated with cancers, researchers have recognized the importance of the functions of GPCRs in tumor biology and paid more attention to GPCRs in many aspects such as molecular machinery ( 87 - 89 ) and tumor-related drug development ( 86 , 90 ). In this study, we found that two key GPCR genes played roles in LUAD by a comprehensive analysis, which indicates that GPCRs provide important functions in tumor biology.…”
Section: Discussionmentioning
confidence: 99%